Benzisoxazole Derivatives: Synthesis and Their Therapeutic Significance in Medicinal Chemistry - Samanth, Mahima; Bhat, Mahesh (Recent Developments in Chemistry and Biochemistry Research Vol. 10, 2025)
Benzisoxazoles and their derivatives have been extensively investigated and applied across various medical fields. These compounds have demonstrated significant therapeutic potential in the management of cardiovascular conditions, including myocardial infarction, hypertension, and hyperlipidemia. Additionally, they have been utilized in the treatment of inflammatory diseases, irritable disorders, and gastrointestinal conditions such as peptic ulcers. Benzisoxazoles also show promise in addressing metabolic disorders, including obesity, diabetes, and metabolic syndrome. Moreover, novel benzisoxazole derivatives exhibit a range of bioactive properties, including anti-inflammatory, anti-cancer, anti-glycation, and antibacterial activities. The continuous advancement in the development of highly active benzisoxazole-based compounds underscores their potential as scaffolds for future therapeutic candidates. This chapter focuses on the synthesis of benzisoxazole derivatives using various methodologies and highlights the significance of this pharmacophore in medicinal chemistry.